Standards and standardization : concepts, methodologies, tools, and applications - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This reference addresses the necessity of a common system of measurement in all technical communications and endeavors, in addition to the need for common rules and guidelines for regulating such enterprises"--Provided by publisher.
Fundamental concepts and theories -- Tools and technologies -- Frameworks and methodologies -- Cases and applications -- Issues and challenges -- Emerging trends.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 04/18/2015).
Keywords: Standardization; Information technology -- Standards; Communication of technical information; Common core; Frameworks and protocols; Interoperability; Open data; Regulations; Security and privacy; Electronic books